Sequencing of ribosome-based amplicons in five isolates Dipodascus Capitus from patients with sinusitis - Hadi, Iman; Abdel-Azeem, Ahmed (University of Thi-Qar Journal of Science, 2024)
Sequencing reactions showed the accurate identity of the investigated samples and revealed that all investigated samples were homologous to Dipodascus capitatus (GenBank acc. no. OW983902.1). The presence of one nucleic acid variant compared with the referring sequences of the D. capitatussequences was demonstrated. The identified variant was represented by a nucleic acid substitution (359A>T) detected in the S5 sample. Meanwhile, the rest of the samples showed a complete homology with the corresponding sequences and did not exhibit any detectable nucleic acid variations in comparison with the D. capitatus reference sequences. It was inferred from the tree that the detected nucleic acid substitutions showed a slight effect of the observed variations on the altering evolutionary positioning of the investigated S5 sample in comparison with the other wild-type sequences. This was due to the positioning of the altered samples in the other positions compared with the wild-type counterparts. It was inferred from the tree that our investigated D. capitatus samples were suited in the immediate vicinity to various strains deposited from various multi-national positions. Furthermore, neighbor phylogenetic distances in this tree indicated a distinct biological diversity of D. capitatus sequences.